2019
DOI: 10.32794/mr11250044
|View full text |Cite
|
Sign up to set email alerts
|

Specificity and nanomolar potency of melatonin on G-protein coupled melatonin MT1 and MT2 receptors expressed in HEK-293T human embryo kidney cells

Abstract: This is a pre-registered study, i.e. a study whose hypotheses and experiments designed to address these hypotheses have been deposited in a database before starting the experiments. The study aims at assessing the Gs versus Gi coupling and the potency of melatonin in the human version of melatonin MT1 and MT2 G-protein-coupled receptors expressed in HEK-293T cells. The results show that these receptors are Gi but not Gs coupled. By using a standard procedure of modulation of 0.5 µM forskolin-induced cAMP level… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 40 publications
1
2
0
Order By: Relevance
“…Thus, activation of these receptors leads to a decrease in cytosolic cAMP levels. We have confirmed that this is the case in single transfected cells (Appendix A Figure A1B,C; see also our recent report [52]), thereby reproducing data reported in References [34,53]. HEK-293T cells expressing D 3 R or MT 1 and incubated with the selective agonists, 7-OH-PIPAT for D 3 and melatonin for MT 1 , led to significant decreases in the forskolin-induced cytosolic cAMP levels.…”
Section: Functional Characterization Of D 3 -Mt 1 Heteroreceptor Compsupporting
confidence: 90%
See 1 more Smart Citation
“…Thus, activation of these receptors leads to a decrease in cytosolic cAMP levels. We have confirmed that this is the case in single transfected cells (Appendix A Figure A1B,C; see also our recent report [52]), thereby reproducing data reported in References [34,53]. HEK-293T cells expressing D 3 R or MT 1 and incubated with the selective agonists, 7-OH-PIPAT for D 3 and melatonin for MT 1 , led to significant decreases in the forskolin-induced cytosolic cAMP levels.…”
Section: Functional Characterization Of D 3 -Mt 1 Heteroreceptor Compsupporting
confidence: 90%
“…Based on prototypic heteromer prints that occur similarly in heterologous expression systems and natural cell lines, and by further confirmation in natural sources by PLA, we discovered novel physiologically relevant receptor-receptor interactions. The D 3 R, expressed in ciliary body epithelial cells, may interact with either MT 1 R or MT 2 R. Canonical coupling of melatonin receptors individually expressed in a heterologous system is to Gi (see References [25,52] and references therein). Dopamine receptors are either coupled to Gs (D 1 and D 5 ) or Gi (D 2 , D 3 and D 4 ).…”
Section: Discussionmentioning
confidence: 99%
“…These are membrane-bound GTP-binding protein (G-protein) coupled receptors (GPCRs). They modulate the activity of the variety of G-proteins, including Giα2, Giα3, Gαq, and Gα11 [20,21]. Moreover, melatonin acts directly to the DNA binding nuclear receptors (NRs) [retinoid-related orphan receptor (ROR)-α/isoforms of nuclear receptors of retinoic acid receptor superfamily (RZR)].…”
Section: Mechanisms Of Actionsmentioning
confidence: 99%